Pengalaman Hidup Seorang Pewaris Bisnis Keluarga dalam Membentuk Kesiapan Diri Melalui Pembelajaran Sosial - Zakia Miftahul Faradisi; Yanladila Yeltas Putra (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Family businesses are a crucial pillar of the economy, contributing significantly to job creation and economic growth. However, the sustainability of family businesses often faces challenges, particularly during the succession process, when the next generation is prepared to take over leadership. The primary issue that arises is how the heir prepares to continue the family business, considering that this process involves not only technical skills but also psychological aspects and social learning. Therefore, this study focuses on the life experiences of a family business heir in developing readiness through social interactions and learning processes within the family environment. This study used a qualitative method with a phenomenological approach. Subjects were selected through purposive sampling, with the criterion of having undergone a business learning process for more than ten years within the family environment. Data collection was conducted through in-depth interviews, allowing researchers to explore the heir's subjective experiences in detail. Data analysis was conducted using the Miles, Huberman, and Saldana model, which includes data reduction, data presentation, and conclusion drawing. The study identified five main themes influencing the heir's readiness. First, the role of the father as the primary mentor in instilling values, work ethic, and business skills. Second, the role of the mother as an emotional supporter and instilling the values ​​of patience and perseverance. Third, the dynamics of the subject's experiences, involving both challenges and successes in the business learning process. Fourth, the process of developing an entrepreneurial mindset, which is formed through early habits. Fifth, the subject's development as a more emotionally, professionally, and socially mature heir. In conclusion, the readiness of a family business heir is formed through a combination of life experiences, social learning within the family, and the role of parents as role models.